Complications following chin laceration reparation using tissue adhesive compared to suture in children. Issue 4 (April 2019) - Ste-Marie-Lestage, Chloé; Adler, Samara; St-Jean, Gabrielle; Carrière, Benoit; Vincent, Matthieu; Trottier, Evelyne D.; Gravel, Jocelyn
Highlights: In children, the rate of dehiscence following repair is higher for chin laceration in comparison to other facial lacerations. The risk of dehiscence is not higher for tissue adhesive in comparison to suture. Tissue adhesive is the reparation method of choice among physicians working in a paediatric emergency department. Abstract: Background: Tissue adhesive is widely used in the emergency department to repair minor lacerations but there exists a debate as to whether it should be used for chin lacerations. The main objective of this study was to evaluate the rate of wound dehiscence of chin lacerations repaired with tissue adhesive in comparison to sutures. Methods: This was a retrospective chart review including all children requiring a facial laceration reparation in a single tertiary care paediatric hospital. The primary outcome was wound dehiscence in the 30 days following reparation, comparing the use of tissue adhesive and sutures. The independent variable of interest was the use of tissue adhesive vs suture. A random sample of charts was reviewed in duplicate to insure reliability of the chart review. Results: Among the 2044 children presenting with a facial laceration requiring an intervention, 1804 (88%) were repaired using tissue adhesive. The laceration was located on the chin in 360 (18%) of patients. The use of tissue adhesive was not statistically associated with a higher risk of dehiscence for all facial lacerations (difference: 0.2; 95%CI: −1.9 to 0.8%), nor for chin lacerations (difference 2.2%; 95%CI: −7.5 to 4.4%). However, the probability of dehiscence was higher for chin laceration in comparison to other localizations (difference of 1.6%; 95%CI: 0.5–3.6%). Conclusion: While the rate of dehiscence was higher for chin lacerations compared to other facial localizations, the risk of dehiscence was not statistically different for chin laceration repaired with tissue adhesive or sutures.